Pattern of Renogram Findings in Patients Attending INMAS, Rajshahi - Hosen, MM Arif; Begum, Nasrin; Ahmed, Parvez; Hossain, Mosharruf; Shah, Kabiruzzaman; Khatun, Shafaly; Chowdhury, Shariful Islam; Shimu, FF (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: Renogram using 99m Tc DTPA ( Technetium diethylene-triamine-pentaacetic acid) with diuretic challenge provides important functional data to assist in the diagnosis and management of suspected renal diseases. Renogram is a routinely performed study at the Institute of Nuclear Medicine and Allied Sciences (INMAS), Rajshahi. This is a referral institute of northern part of the country. The objective of this study was to see the pattern of renogram findings in INMAS, Rajshahi. Patients and Methods: A total 98 patients underwent renogram using Tc99m-DTPA with diuretic challenge from July 2015 to June 2016 were included in this study and a retrospective observation study was done. A total 98 (male to female ratio 1: 0.75) with a mean age 38.6 ± 18.5 years (age range 02 months to 80 years) patients data were analyzed. Some additional imaging and biochemical tests were available at the time of renography eg. Ultrasonography of renal system and serum creatinine level in all cases, X-ray of KUB (kidney-ureter-bladder) region in 44 cases, IVU (intravenous urogram) in 38 cases and urinary routine and microscopic examination in 32 cases only were done. Results: Renogram findings showed obstructive renal disease in single or both kidneys in 57.14% cases, non-obstructive abnormalities in single or both kidneys in 28.57% cases and normal study in 14.29% cases. Conclusion: In this study a variety of renographic diagnosis was observed, most common was obstructive renal disease in 57.14% cases and non-obstructive abnormalities in 28.57% cases. Bangladesh J. Nuclear Med. 19(2): 116-119, July 2016